Yoga is effective for treating chronic pain in veterans with Gulf War Illness at long-term follow-up - Santiago Allende; Danielle C. Mathersul; Jay R. Schulz-Heik; Timothy J. Avery; Louise Mahoney; Peter J. Bayley (BMC, 2023)
Abstract Background Clinical Practice Guidelines for Gulf War Illness (GWI) recommend integrative health approaches such as yoga for relief from symptoms, yet little is known about the long-term efficacy of yoga in reducing symptoms of GWI. Here, we evaluated the long-term efficacy of yoga and cognitive-behavioral therapy (CBT) chronic pain treatment in a randomized controlled trial (RCT) of 75 Veterans (57 men, 42-71 ± 7.1 years of age) with Gulf War Illness (GWI). Methods Participants received either 10 weeks of yoga or 10 weeks of CBT for chronic pain. The primary outcome measures were pain severity, and pain interference (Brief Pain Inventory-Short Form). The secondary outcome measures were fatigue, as indicated by a measure of functional exercise capacity (6-Minute Walk Test), depression, autonomic symptom severity, and quality of life. Piecewise linear mixed models were used to examine study hypotheses. Results Compared to the CBT group, yoga was associated with greater reductions in pain severity during the 6-month follow-up period (group × time interaction: b = 0.036, se = 0.014, p = .011). Although we did not find between-group differences in the other primary or secondary outcome measures during follow-up (p's > 0.05), exploratory analyses revealed within-group improvements in pain interference, total pain (an experimental outcome variable which combines pain severity and interference), and fatigue in the yoga group (p's < 0.05) but not in the CBT group. Conclusions This is the first study to report long-term follow-up results of yoga as a treatment for GWI. Our results suggest that yoga may offer long-term efficacy in reducing pain, which is a core symptom of GWI. Trial registration Secondary analyses of ClinicalTrials.gov NCT02378025.